A Remark about Time-Analyticity of the Linear Landau Equation with Soft Potential (Analysis in Theory and Applications, 2024)
In this note, we study the Cauchy problem of the linear spatially homogeneous Landau equation with soft potentials. We prove that the solution to the Cauchyproblem enjoys the analytic regularizing effect of the time variable with an $L^2$ initialdatum for positive time. So that the smoothing effect of Cauchy problem for the linear spatially homogeneous Landau equation with soft potentials is similar to the heatequation.